2016
DOI: 10.7287/peerj.preprints.1754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging and serum MCP-1 are associated with gut microbiome composition in a murine model

Abstract: Introduction Age is the primary risk factor for major human chronic diseases, including cardiovascular disorders, cancer, type 2 diabetes, and neurodegenerative diseases. Chronic, low-grade, systemic inflammation is associated with aging and the progression of immunosenescence. Immunosenescence may play an important role in the development of age-related chronic disease and the widely observed phenomenon of increased production of inflammatory mediators that accompany this process, referred to as “inflammaging… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 3 publications
4
23
0
Order By: Relevance
“…Gut microbial composition were analyzed using fresh fecal samples collected at weeks 0, 4, and 7 of the experimental period (Figure 1). Individually, none of the NOR, HE, and HO groups showed intra‐group similarity in the fecal bacterial distribution patterns among these observation periods (Figure S4A) and were consistent with the previous reports 32‐34 . Moreover, Chao 1 analysis and the observed OTUs from 16S rRNA sequencing data revealed that the alpha diversity of the gut microbial community did not differ significantly among the aforementioned experimental groups at any measurement time points (weeks 0, 4, and 7; Figure S2A).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Gut microbial composition were analyzed using fresh fecal samples collected at weeks 0, 4, and 7 of the experimental period (Figure 1). Individually, none of the NOR, HE, and HO groups showed intra‐group similarity in the fecal bacterial distribution patterns among these observation periods (Figure S4A) and were consistent with the previous reports 32‐34 . Moreover, Chao 1 analysis and the observed OTUs from 16S rRNA sequencing data revealed that the alpha diversity of the gut microbial community did not differ significantly among the aforementioned experimental groups at any measurement time points (weeks 0, 4, and 7; Figure S2A).…”
Section: Resultssupporting
confidence: 90%
“…Individually, neither the SHAM nor the SHO group showed any intra‐group similarity in the fecal bacterial distribution patterns among weeks 0, 4, and 7 of the experimental period (Figure S4B), in agreement with the previous studies 32‐34 . Furthermore Chao‐1 analysis and the OTUs observed from 16S rRNA sequencing data showed that the alpha diversity of gut microbial communities did not differ significantly between SHAM and SHO groups at all time‐points of measurements (weeks 0, 4, and 7; Figure S2B).…”
Section: Resultssupporting
confidence: 90%
“…S1), indicating that descendants of this genus may have recently evolved traits that 233 contribute to their differential association with canine behavior. This observation underscores 234 prior work that indicates that the functional associations between gut bacteria and mammals may 235 rapidly evolve among bacteria (Conley et al, 2016a). 289 that closely related clades can manifest opposite patterns of association with behavior, such as 290 that of Turicibacter.…”
mentioning
confidence: 60%
“…An example of this is the 42 increase in the number of facultative anaerobes and a decline in the proportion of beneficial bacteria 43 associated with aging (1,2). This shift in the microbial composition leads to the accumulation of toxic 44 microbial metabolites in the body causing inflammation, oxidative stress and contributing to various 45 diseases prominent in the aging condition (3).…”
mentioning
confidence: 99%